CORRESSPONDENCE SKILL - Desi Ratna Sari; Nurul Fadilah (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2022)
In the business world, correspondence is important. Internal and external communication will be effective if the letter is written using good and correct language. In relation to external communication, the figure of the letter itself embodies the company's image on paper. Besides a distinctive patterned logo, a carefully planned and carefully written letter reflects the company's pride, pride and concern for high quality. The style of correspondence in the business world is not static.